2017
DOI: 10.5194/acp-17-11177-2017
|View full text |Cite
|
Sign up to set email alerts
|

Shift of subtropical transport barriers explains observed hemispheric asymmetry of decadal trends of age of air

Abstract: Abstract. In response to global warming, the BrewerDobson circulation in the stratosphere is expected to accelerate and the mean transport time of air along this circulation to decrease. This would imply a negative stratospheric age of air trend, i.e. an air parcel would need less time to travel from the tropopause to any point in the stratosphere. Age of air as inferred from tracer observations, however, shows zero to positive trends in the northern mid-latitude stratosphere and zonally asymmetric patterns. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
6
37
1
Order By: Relevance
“…Recently, Stiller et al (2017) found the same meridional pattern in N 2 O from the CLaMS CTM model, driven by the ERA-Interim reanalysis, and explored the hemispheric symmetry in the AoA, confirming a southward displacement of the stratospheric circulation pattern between the potential temperature levels of 500 and 800 K. Additionally, Garfinkel et al (2017), using the GEOSCCM model, also found an increase in the Northern Hemisphere AoA for the period after 1992 when including the stratospheric aerosols and ODS evolution in the simulation. The positive trend peaks between 20 and 30 • N and extends from 20 to 40 km.…”
Section: Discussion Of the Hemispheric Asymmetrymentioning
confidence: 99%
“…Recently, Stiller et al (2017) found the same meridional pattern in N 2 O from the CLaMS CTM model, driven by the ERA-Interim reanalysis, and explored the hemispheric symmetry in the AoA, confirming a southward displacement of the stratospheric circulation pattern between the potential temperature levels of 500 and 800 K. Additionally, Garfinkel et al (2017), using the GEOSCCM model, also found an increase in the Northern Hemisphere AoA for the period after 1992 when including the stratospheric aerosols and ODS evolution in the simulation. The positive trend peaks between 20 and 30 • N and extends from 20 to 40 km.…”
Section: Discussion Of the Hemispheric Asymmetrymentioning
confidence: 99%
“…In particular, Ray et al (2014) and Ploeger et al (2015) find that changes in isentropic mixing have contributed to recent observed mean age trends in the LS. Most recently, Stiller et al (2017) suggest that these changes are connected to a southward shift of the Brewer-Dobson circulation. As such a shift may also imply changes in lower stratospheric mixing, however, this finding is not necessarily inconsistent with the ones discussed in the earlier studies.…”
Section: Geophysical Research Lettersmentioning
confidence: 99%
“…Bönisch et al () highlighted the importance of structural changes in the residual circulation showing decoupled changes in the deep and shallow branches at the beginning of the 21st century. Moreover, the AoA estimates reveal a robust interhemispheric asymmetry in the trends over 2002–2012 (Haenel et al, ; Khaykin et al, ; Mahieu et al, ; Stiller et al, , ). It remains unclear what has led to these changes in the trends before and after 2000.…”
Section: Introductionmentioning
confidence: 99%